Postoperative visual and auditory hallucinations after cardiac surgery: VAACS umbrella study - Abu Khadija, Haitham; Abu Hamdeh, Nizar; Najajra, Duha; Othman, Wafiq; Abdul-Hafez, Hamza A.; Zahran, Anwar; Heih, Omar; Fraitekh, Yahya Z.; Masu'd, Mohammad; Awwad; Filho, Idiberto José Zotarelli [UNESP]; Zayed, Alaa; et al. (Elsevier, 2025)
Background Hallucinations are underrecognized neuropsychiatric complications after cardiac surgery. Data on incidence and type-specific predictors in coronary artery bypass grafting (CABG) and valvular surgery are limited. Methods We conducted a multicenter prospective cohort study (September 2022 to May 2025) across West Bank cardiac surgery centers. A total of 1332 adults (997 CABG, 335 valve) were assessed daily for 7 days postoperatively using the Questionnaire for Psychotic Experiences. Predictors of visual and auditory hallucinations evaluated with Cox proportional hazards models. Results Visual hallucinations occurred in 11.5 % of CABG patients and 10.0 % of valve surgery patients, while auditory hallucinations were reported in 7.0 % and 5.0 %, respectively. In the CABG group, the multivariable Cox regression models stratified by hospital showed that auditory hallucinations were significantly associated with lower left ventricular ejection fraction (HR = 1.05 per 1 % decrease; 95 % CI 1.01–1.09), longer aortic cross-clamp time (HR = 1.01 per minute; 95 % CI1.0004–1.02), and immunosuppressive therapy (HR = 4.81; 95 % CI 1.13–20.53). Postoperative blood transfusion was associated with an increased risk of visual hallucinations in univariate analysis (HR = 1.87; 95 % CI 1.05–3.33), but the association became borderline after adjustment (HR = 1.97; 95 % CI 0.95–4.09). Among the valve surgery cohort, the hospital-stratified models indicated that prolonged postoperative ventilation was independently protective against visual hallucinations (adjusted HR = 0.78; 95 % CI 0.68–0.90), whereas noradrenalin use (adjusted HR = 6.07; 95 % CI 2.18–16.93) and immunosuppressive therapy (adjusted HR = 5.13; 95 % CI 1.14–23.09) markedly increased the risk. For auditory hallucinations in valve surgery patients, adrenaline exposure emerged as a significant independent predictor (adjusted HR = 3.40; 95 % CI 1.21–9.54. Conclusions Postoperative hallucinations affected ~1 in 10 patients; visual hallucinations were more frequent, auditory hallucinations linked to stress and medications, with risks varying by surgery type, supporting tailored monitoring and prevention.